PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL INTERVENING (Studi pada PNS di Kecamatan Watukumpul Kabupaten Pemalang) - Ahmad Mubarak; Susetyo Darmanto (MAKSIMUM, 2015)
This study aimed to determine the effect of transformational leadership style on performance and organizational commitment as an intervening variable, the influence of organizational culture on employee performance and organizational commitment as an intervening variable, determine the effect of transformational leadership style directly to employee performance, and determine the influence of organizational culture directly to the employee performance. The population in this study were all employees of the Watukumpul districtl. By using the census method, all employees amounted to 140 people were carried out as the  sample. Analysis  data were analyzed using path analysis. Based on the research results it could be concluded that there was  significantly and positive effect of  transformational leadership style and organizational culture. Transformational leadership style and organizational culture also had significantly and positive effect on Organizational commitment. And finally there was significantly and positive effect of organiztional commitment.The research also showed that Organizational commitment had a mediating role between  transformational leadership style, Organizational culture and employee performance. Keyword: Transformational Leadership Style, Cultural Organization,Organizational Commitment, Employee Performance